2022
DOI: 10.5312/wjo.v13.i11.955
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trends of orthopedic services due to the COVID-19 pandemic: A review

Abstract: As of June 10, 2022, the World Health Organization has recorded over 532 million documented coronavirus disease 2019 (COVID-19) [(Coronavirus) SARS-CoV-2] cases and almost 6.3 million deaths worldwide, which has caused strain on medical specialties globally. The aim of this review is to explore the impact that COVID-19 has had on orthopedic practices. Providers observed a rapid decline in the number of orthopedic patients’ admissions due to cancellation of elective procedures; however, emergent cases still req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Considering the reallocation of healthcare resources during the COVID-19 pandemic, the primary objective was to provide medical care to the maximum number of people while preventing potential viral transmission that could arise from surgical treatment delays [ 50 ]. The decrease in time to surgery, as reported by some authors, including the present study, exemplifies the efforts made to prioritize the urgent treatment of hip fractures [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the reallocation of healthcare resources during the COVID-19 pandemic, the primary objective was to provide medical care to the maximum number of people while preventing potential viral transmission that could arise from surgical treatment delays [ 50 ]. The decrease in time to surgery, as reported by some authors, including the present study, exemplifies the efforts made to prioritize the urgent treatment of hip fractures [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in time to surgery also possibly highlights the benefits of quarantine measures for healthcare system capacity, as they effectively offloaded theaters by reducing surgical trauma, due to restricted mobility, and by canceling elective surgical cases. However, the productivity of the theatre, the allocation of surgical and anesthetic teams, and even the adaptation to complicated aerosol-generating procedures (AGPs) are factors that seem to have affected some hospitals, resulting in delays in operative treatment [ 34 ], while others have managed to overcome these challenges and maintain a high standard of healthcare services [ 38 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Pogoreli et al discovered a significant increase in delayed presentations and care among patients with testicular torsion during the COVID-19 pandemic [ 9 ]. Furthermore, orthopedic surgery, considered a relatively non-life-threatening condition, experienced delays in stages to alleviate the strain on healthcare services [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been observed that those overall reductions resulted often from considerable reductions in RTIs [ 16 – 19 ] and, to some extent, in sport and leisure related injuries [ 19 ]. The most common explanation for lowered numbers is that of reduced hazard exposure as a consequence of confinement and mobility restrictions [ 16 , 19 , 23 , 24 ]. While the explanation is very plausible [ 16 , 24 ], it cannot help to explain a rise in the volume of injuries during the same restriction period shown in a few studies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, restriction periods could also be characterized by shifts in injury patterns [ 18 , 19 , 23 ], reflecting changes in exposure. Most typically, while RTIs went down, confinement measures were associated with an increase in the number (or proportion) of burns [ 26 – 28 ] and violence-related injuries [ 21 , 22 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%